ORGANIZAÇÃO E FUNCIONAMENTO DE UM PROGRAMA DE SEGUIMENTO DOS RECÉM-NASCIDOS DE RISCO: PERSPECTIVA DE GESTORES, PROFISSIONAIS DE SAÚDE E FAMILIARES - Patricia Harumi Ueno (2024)
Every baby born before 37 weeks of gestation is considered preterm and requires health monitoring by a multidisciplinary team. Additionally, some full-term babies also need special care due to birth conditions or because they are at risk of death, classified as high-risk newborns. In recent decades, there has been a significant improvement in the survival of preterm newborns after hospital discharge. However, these babies require differentiated attention and systematic follow-up by a multidisciplinary team to ensure specialized care and continuity of care in outpatient and home settings. The aim was to analyze a high-risk newborn follow-up program from the perspective of management, healthcare professionals, and families. This is a descriptive study with a qualitative approach. Semi-structured interviews were conducted with managers, healthcare professionals, and families of high-risk newborns discharged from neonatal units of a public hospital in Campo Grande, MS. The interviews took place from March to June 2023, recorded, transcribed verbatim, and subjected to content analysis. The study included two managers, two healthcare professionals, and nine family members. The data were organized into a central category "Organization of the service to guarantee assistance to high-risk newborns and families" consisting of three subcategories: "Functioning of the high-risk newborn follow-up program", "Family reception", and "Difficulties faced and suggestions for improving care". The program operates with only two healthcare professionals, indicating a lack of a complete multidisciplinary team in the outpatient clinic. Additionally, there is no sharing of care after the baby's discharge with the primary care team. It was also observed that the distance from home to care facilities is a factor that may contribute to care discontinuity. On the other hand, families unanimously praised the good care and relationship with the pediatrician who attends the program. Therefore, to enhance the effectiveness of follow-up, it is necessary to address issues such as protocol implementation, continuous attention, building bonds between healthcare professionals and families, and communication among teams to improve the quality of care.